ECAR Study of Faculty and Information Technology, 2014 - Dahlstrom, Eden; Brooks, Christopher D. (Educause Center for Applied Research (ECAR), 2014)
ECAR collaborated with 151 institutions to collect responses from 17,451 faculty respondents across 13 countries about their technology experiences. Key Findings Selected findings are below. See the report for a comprehensive list. Faculty recognize that online learning opportunities can promote access to higher education but are more reserved in their expectations for online courses to improve outcomes. Faculty interest in early-alert systems and intervention notifications is strong. The majority of faculty are using basic features and functions of LMSs but recognize that these systems have much more potential to enhance teaching and learning. Faculty think they could be more effective instructors if they were better skilled at integrating various kinds of technology into their courses. Faculty recognize that mobile devices have the potential to enhance learning.